O ensino de dança na educação física escolar: uma proposta metodológica para os anos iniciais do ensino fundamental - Brandão, Flávia Ramalho Monteiro (2024)
The teaching of Dances in school Physical Education classes, as well as other specific contents of this curricular component, often presents in pedagogical practice only procedural aspects of the content, the "knowing how to do", however, the current curricular guidelines that guide Education, the BNCC, directs a teaching and learning process beyond the "knowing how to do", aiming at the global formation of the student through concepts, attitudes and values. Given the lack of academic production on this subject, the aim of this study is to develop a methodological teaching proposal for the content of Dances of Brazil and the World in the early years of elementary school, integrated into the Physical Education curriculum, in accordance with the legal guidelines and the particular needs of the educational environment. From this perspective, a qualitative study was undertaken, based on the precepts of action research and supported by the Pedagogical Intervention Project developed during the Professional Master's Degree in Teaching in Basic Education of the Stricto Sensu Postgraduate Program at CEPAE/UFG, which was configured into the educational product entitled "Dance in the context of Physical Education: Dances from Brazil and the world". Participant observation, the Field Diary, audiovisual recordings and questionnaires were used as instruments for producing and collecting data. In order to analyze and interpret the data, the Field Diary entries were taken into account, as well as observations in class, audiovisual recordings and entries written by the students in response to the questionnaires. Given the constant changes, especially with the implementation of the BNCC, this study is an important theoretical and methodological support for teachers involved in the teaching of Physical Education in the early years, with the aim of contributing to a better performance in the face of the numerous challenges that arise in everyday school life, and thus guaranteeing meaningful learning and the principles of an integral education, which seeks to develop broad skills and competencies in students, making them protagonists in the educational process. As a result, this study shows that the implementation of Dance in school Physical Education classes, from the perspective of the dimensions of knowledge and guided by the current curriculum guidelines, the BNCC, plays a fundamental role as a pedagogical activity that can be worked on in its various aspects, providing students with emotional, physical, intellectual and social benefits. This content helps in a positive way to build the individual's knowledge in relation to the body culture of movement and to recover historical and socio-cultural aspects of both the society in which he is inserted and the world